2003
DOI: 10.1007/s00330-003-1855-2
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution endovaginal MR imaging in stress urinary incontinence

Abstract: The causes of stress urinary incontinence are not completely known. Recent papers have stressed the importance of more anatomical information, which may help to elucidate the mechanism of stress urinary incontinence. The purpose of this study was to evaluate the prevalence of lesions of the urethral support mechanism and lesions (defects and scars, thinning) of levator ani muscle with endovaginal MRI in a case-control study. Forty women (median age 52 years, age range 40-65 years)--20 patients with stress urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
(29 reference statements)
0
26
0
Order By: Relevance
“…Studies show that women with stress urinary incontinence often have weak or asymmetrical contraction of the pelvic floor. 3,4 Using electromyography Kenton and Brubaker noted that the pelvic floor muscles and RHB sphincter make independent contributions to urinary continence and work together to facilitate urethral closure by a reflex muscle contraction. 30 We propose that the PRM, a component of the pelvic floor muscles, has a direct role in the genesis of UP during reflex contractions of the abdominal wall and pelvic floor muscles, the latter of which are associated with increases in intra-abdominal pressure (stress maneuvers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that women with stress urinary incontinence often have weak or asymmetrical contraction of the pelvic floor. 3,4 Using electromyography Kenton and Brubaker noted that the pelvic floor muscles and RHB sphincter make independent contributions to urinary continence and work together to facilitate urethral closure by a reflex muscle contraction. 30 We propose that the PRM, a component of the pelvic floor muscles, has a direct role in the genesis of UP during reflex contractions of the abdominal wall and pelvic floor muscles, the latter of which are associated with increases in intra-abdominal pressure (stress maneuvers).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies demonstrated that women with stress urinary incontinence often have weak or asymmetrical contractility of the pelvic floor muscles, 3,4 which implies that the latter has a role in urinary continence. Studies show that voluntary pelvic floor muscle contractions have a significant impact on UP.…”
mentioning
confidence: 99%
“…MRI findings related to SUI caused by UH and ISD in women have been descri bed [9] . Previous studies of MRI in female patients with SUI were focused on the assessment of lesions of the urethral support mechanism [10] , defects of the levator ani muscle [11,12] , and paravaginal fascia [13] , as well as on the kinematics of pelvic floor muscles function [14] . To date, however, the role of MRI in the specific diagnosis of SUI caused by UH and/or ISD has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…UH was diagnosed if the angle changed over 30 degrees between the rest and strain (as per definition of hypermobility) [11] . The bladder neck descent was measured as a distance (cm) between its position at rest and strain in reference to the pubococcygeal line (PCL, a line drawn from the inferior margin of the pubic bone to the last coccygeal joint).…”
Section: Mri Interpretationmentioning
confidence: 99%
“…The angle of the urethral axis is abnormal when it is greater than 30 degrees from the vertical [7]. Urethral hypermobility is seen in patients with symptoms of stress urinary incontinence and abnormalities of the urethral support ligaments and levator ani muscle are seen on high-resolution imaging [18]. These include defects in the levator muscle and scar tissue.…”
Section: Urethramentioning
confidence: 96%